2017
DOI: 10.1038/s41598-017-02400-0
|View full text |Cite
|
Sign up to set email alerts
|

A seven-million-year hornblende mineral record from the central Chinese Loess Plateau

Abstract: Previous studies of the late Cenozoic erosion rate have yielded different views—long-term stable rates or a significant increase at climate transitions—leading to uncertainty concerning the hypothesized global erosion rate controlled by either tectonic uplift or climatic changes. Here, we present a seven-million-year hornblende mineral record along the Lingtai section of the Chinese Loess Plateau. By examining the spatial distribution of hornblende minerals in seven desert basins, which are potential loess sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…Chlorite concentration in the fine versus coarse grain-size fractions in the Lingtai section, which is a proxy indicator for atmospheric circulation. Muscovite (this study) (b) and hornblende (c) (He et al, 2017) concentrations along the same section. (d) Magnetic susceptibility values (Chen et al, 2006).…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…Chlorite concentration in the fine versus coarse grain-size fractions in the Lingtai section, which is a proxy indicator for atmospheric circulation. Muscovite (this study) (b) and hornblende (c) (He et al, 2017) concentrations along the same section. (d) Magnetic susceptibility values (Chen et al, 2006).…”
Section: Resultsmentioning
confidence: 68%
“…Variations in hornblende and muscovite minerals in the same profile provide further evidence that chemical weathering during diagenesis played a minor role in shaping the glacial–interglacial chlorite pattern. Our previous studies have shown that hornblende concentrations are between 0 and 2.5% over the past 1.2 Ma in the Lingtai section (He et al, 2017), a range equivalent to that of the chlorite concentration. However, the hornblende concentrations do not display glacial–interglacial changes (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The abundance of amphibole indicates prominent contributions from basement rocks [24,47], with the amphibole series forming in a wide range of temperature and pressure conditions in igneous and metamorphic rocks [48]. A ratio of amphibole versus total heavy minerals has been used to reflect past changes in the origin of loess from the central Chinese Loess Plateau [49]. Because more than 73% of the heavy-mineral fraction is composed of amphibole plus epidote in Yellow River terraces, we here use the ratio between these two dominant minerals as a tracer of provenance change.…”
Section: Heavy-mineral Assemblagesmentioning
confidence: 99%